Establishment of a sensitive UPLC-MS/MS method to quantify safinamide in rat plasma - Ying Wang; Guan-An Zhao; Xia Li; En Zhang; Wei Tan; Jia-qi Chen (Frontiers in Pharmacology, 2023)
A fast, simple, and sensitive ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method was established for the quantification of safinamide in rat plasma. Plasma samples were treated with acetonitrile for protein precipitation, and diazepam was used as an internal standard (IS). The analytes were separated on an Acquity UPLC C18 (2.1 mm × 50 mm, 1.7 μm) chromatographic column with gradient elution using a mobile phase (0.1% formic acid-acetonitrile). Then, the eluates were detected by electrospray ionization (ESI) in positive ion mode. The analytes were quantified by multiple reaction monitoring (MRM) using the transition m/z 303.3→215.0 of safinamide and m/z 285.0→154.0 of IS. Safinamide had good linearity in the concentration range of 1.0–2000 ng/mL, and the lower limit of quantitation (LLOQ) was 1.0 ng/mL. The intra- and inter-day precision and accuracy of safinamide were less than 7.63%, while the average recovery rate was 92.98%–100.29%. The method was validated to be stable and had low noise, short chromatographic run time, wide linear range, small sample volumes, low sample injection volumes, and high sensitivity. Therefore, it can be used in pharmacokinetics and preclinical and clinical studies.